2021
DOI: 10.1038/s41598-021-94464-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diets associated with dilated cardiomyopathy in dogs using foodomics analysis

Abstract: Dilated cardiomyopathy (DCM) is a disease of the heart muscle that affects both humans and dogs. Certain canine diets have been associated with DCM, but the diet-disease link is unexplained, and novel methods are needed to elucidate mechanisms. We conducted metabolomic profiling of 9 diets associated with canine DCM, containing ≥ 3 pulses, potatoes, or sweet potatoes as main ingredients, and in the top 16 dog diet brands most frequently associated with canine DCM cases reported to the FDA (3P/FDA diets), and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 58 publications
(82 reference statements)
2
38
0
Order By: Relevance
“…The results of this study showed some similarities to a publication that applied metabolomic profiling to food samples (foodomics). 15 For example, the foodbased study also found lower vitamins and cofactors and higher xenobiotics in diets associated with DCM, compared with diets not associated with DCM, which was similar to our findings for these metabolites in the blood of dogs eating GF and GI diets. 15 While it is not surprising that biochemical compounds found in food would be detectable in the blood of dogs, the metabolomic profile is not expected to be identical to the foodomic profile because of changes that biochemical compounds undergo associated with absorption and metabolism.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of this study showed some similarities to a publication that applied metabolomic profiling to food samples (foodomics). 15 For example, the foodbased study also found lower vitamins and cofactors and higher xenobiotics in diets associated with DCM, compared with diets not associated with DCM, which was similar to our findings for these metabolites in the blood of dogs eating GF and GI diets. 15 While it is not surprising that biochemical compounds found in food would be detectable in the blood of dogs, the metabolomic profile is not expected to be identical to the foodomic profile because of changes that biochemical compounds undergo associated with absorption and metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…The top differentiating metabolite (X-25419, which, in the GF group, was 6.65 times that in the GI group at baseline) was reported to be higher by a factor of 7.67 fold in dog foods associated with DCM, compared with dog foods that have not been associated with DCM in the previous foodomics study, suggesting that diet is the source of this metabolite in the blood of dogs in the GF group. 15 This unnamed compound was also present in GI diets but to a lesser degree. A study 18,19 in people identified X-25419 in blood and urine to be associated with fish and olive oil ingestion, and a study 20 of dogs with mitral valve disease found that X-25419 was significantly different between healthy dogs predisposed to heart disease and dogs with mild heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same trial, 5-AVAB was associated with the ratio of early mitral inflow velocity and mitral annular early diastolic velocity, a novel indicator for heart failure with preserved ejection fraction [67,68]. In addition, investigators examined a cardiac condition called dilated cardiomyopathy, a disease affecting human and dog hearts, and they reported that dog diets associated with this condition contain a higher level of 5-AVAB compared with the diets that are not associated with it [69]. Somewhat at odds with these results, it has been demonstrated that 5-AVAB reduces β-oxidation in cardiomyocytes by decreasing the carnitine level via inhibition of the cell membrane carnitine transporter (Figure 2) [45].…”
Section: Heart Muscle Regulationmentioning
confidence: 99%
“…A diverse array of causes for DCM have been identified for both humans and canines including genetic mutations [1,20], infection and autoimmunity [21][22][23][24], toxin exposure like alcohol and cytostatics [25,26], metabolic dysfunction and nutritional deficiencies [26][27][28], and even pregnancy [24,29]. Nevertheless, idiopathic and familial DCM are among the most frequently reported causes [12].…”
Section: Clinical Aspects Of Canine and Human Dcmmentioning
confidence: 99%